Association between the rs2288947 polymorphism of the lncRNA TINCR gene and the risk of recurrent miscarriage in a Southern Chinese population. Issue 6 (23rd May 2019) - Huang, Wendong; Zhou, Huazhong; Pi, Lei; Xu, Yufen; Fu, LanYan; Yang, Yanfang; Che, Di; Gu, Xiaoqiong
Abstract: Studies have shown that many genes that regulate cell migration are associated with susceptibility to recurrent miscarriage. Terminal differentiation‐induced non‐coding RNA (TINCR) regulates the migration and invasion of a variety of tumor cells and is associated with susceptibility to various diseases. However, whether the lncRNA TINCR polymorphism is associated with susceptibility to recurrent miscarriage is unclear. Therefore, we investigated the relationship between the rs2288947 A > G polymorphism of the lncRNA TINCR and susceptibility to recurrent abortion. We recruited 248 recurrent spontaneous abortion patients and 392 healthy control subjects from the Southern Chinese population and used the TaqMan method for genotyping. There was no evidence that this polymorphism is associated with recurrent miscarriage (AG vs AA: adjusted OR = 0.904, 95% CI = 0.647‐1.264, P  = 0.5552; GG and AA: adjusted OR = 0.871, 95% CI = 0.475‐1.597, P  = 0.6542; dominant model: AG/GG vs AA: adjusted OR = 0.898, 95% CI = 0.653‐1.236, P  = 0.5101; and recessive model: GG vs AA/AG: adjusted OR = 0.910, 95% CI = 0.505‐1.639, P  = 0.7527). The stratified analysis also showed no significant associations. This study suggests that the rs2288947 A > G polymorphism of the lncRNA TINCR may not be associated with recurrent miscarriage in a Southern Chinese population. A larger multicenter study is needed to confirm our conclusions.